Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Terhadap Pemahaman Konsep Matematis Siswa Kelas VII SMP Muhammadiyah 6 Padang - Trisno, Ton; Rahmi, Rahmi; Mardiyah, Ainil (STKIP PGRI Sumbar, 2013)
This background research is based on the studentsâ concept comprehension of mathematical which still lower so as impact it makes low Â their learning result to the students at Junior High School Â Muhammadiyah 6 Padang in seventh class. This research aims to know what is comprehension of mathematical studentsâ concept by applying model study of type cooperative of Team Assisted Individualization (TAI) better than comprehension of mathematical studentsâ concept with conventional study at students Junior High School Muhammadiyah 6 Padang in seventh class. The type of this research is an experiment research with take of random to subject. Research population is all students Junior High School Muhammadiyah 6 Padang in seventh class, period 2012 / 2013. Intakes of samples are conducted randomly. Chosen class is class of VII.2 as experiment class and class of VII.3 as control class. Research instrument is final test which in form of essays with reliabilities test is 0,91. Technique analyses data which is use test of t one side constructively MINITAB.Â Based on the result of hypothesis test obtained P-value equal to its 0,008 meaning smaller than Î± that is 0,05. So that can be concluded that comprehension of mathematical studentsâ concept by applying model study of type cooperative of Team Assisted Individualization (TAI) better than comprehension of mathematical studentsâ concept with conventional study at student Junior High School Muhammadiyah 6 Padang in seventh class.